2012
DOI: 10.1021/jo3015769
|View full text |Cite
|
Sign up to set email alerts
|

The Intramolecular Allenolate Rauhut–Currier Reaction

Abstract: An intramolecular Rauhut-Currier reaction utilizing alkynoates as the initial conjugate acceptor affords densely functionalized 5- and 6-membered rings from ynoate-enoate, ynoate-enenitrile, and alkynyl sulfone-enenitrile substrates. Trialkylphosphines catalyze the reaction, and TMSCN serves as a pronucelophile to effect turnover of the catalyst and the formation of a second C-C bond. Because of the highly electrophilic alkyne acceptor, this reaction yields products that cannot be easily accessed from the trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In 2012, MacKay and co-workers reported the synthesis of functionalized 2-cyanocyclopentenes through the α-addition–Michael addition pathway of enynes (Scheme ). The reactions gave 2-cyanocyclopentenes in good yields from substrates featuring various electron-withdrawing groups (i.e., ester, nitrile, and sulfone).…”
Section: Nucleophilic Phosphine Catalysis Of Acetylenesmentioning
confidence: 99%
“…In 2012, MacKay and co-workers reported the synthesis of functionalized 2-cyanocyclopentenes through the α-addition–Michael addition pathway of enynes (Scheme ). The reactions gave 2-cyanocyclopentenes in good yields from substrates featuring various electron-withdrawing groups (i.e., ester, nitrile, and sulfone).…”
Section: Nucleophilic Phosphine Catalysis Of Acetylenesmentioning
confidence: 99%
“…A plausible mechanism for this new process involving a Michael-type addition and a double cyclization is depicted in Scheme . In this case, the allenylmetallate Ia , resulting from the addition of the propargylmalonate enolate to the Fischer carbene, would undergo an intramolecular 5- exo cyclization by nucleophilic attack over the C–C triple bond to give cyclic metallatriene V (cyclization d) . The latter readily would undergo cyclopentannulation and proton rearrangement to cyclopentadienyl anion intermediate VI (cyclization a), and then protonation would give rise to compounds 6 and 7…”
Section: Resultsmentioning
confidence: 99%
“…In a different and interesting kind of IRC reaction, MacKay et al reported phosphine catalyzed ring closure along with addition of cyanide across alkyne (Scheme 34). 45 Although end product resembles to be result of double Michael addition initiated by CN but reaction doesn't proceed in the absence of phosphine catalyst. In the proposed mechanism initial attack of phosphine across triple bond was followed by ring closure reaction.…”
Section: Irc-fundamental Developmentsmentioning
confidence: 99%